A facile synthesis of a uniform constitution of three-dimensionally ordered macroporous TiO2–carbon nanocomposites with hierarchical pores for lithium ion batteries1. Issue 13 (7th April 2015) - Song, Lihong; Li, Ling; Gao, Xin; Zhao, Jiaxin; Lu, Ting; Liu, Zhi
<x xml:space="preserve">Abstract</x> A novel 3DOM TiO2–carbon nanocomposite is fabricated via a simple multicomponent infiltration of three-dimensionally ordered templates, and exhibits superior lithium ion storage performance.